Vivência do profissional de saúde na crise psiquiátrica com comportamento conflituoso: um estudo fenomenológico - Edson André Pereira Hilário (2023)
The conflictive behavior in the context of mental health crisis is not rare, but it is veiled and little discussed, being an obstacle to an effective implementation of psychiatric reform. In some cases, such behavior is the form of presentation of anguish, insecurity, perplexity, fear, and dissatisfaction. Some studies suggest that the way the professional reacts emotionally to the patient's behavior, as well as the attribution that gives the origin of this behavior, the structure of the service, among others, that may influence the way this behavior is handled, leading to the use of coercive strategies. By means of a phenomenological study, we sought to understand how professionals experience the context of the psychiatric crisis with the manifestation of the conflictive behavior, identifying the significant elements in the professionals' perspectives that emerge from this experience and the difficulties pointed out by them, that influence the care provided. The intentional sample is made up of 12 health professionals from a 24-hour Psychosocial Care Center who fit the defined inclusion criteria. The descriptions of the experiences were obtained through open interviews, addressing the aspects of the experience. The full transcripts of the interviews were analyzed according to the descriptive phenomenological method of Giorgi and Sousa (2010). Composing the overall structure of meanings, six essential constituents were identified: (1) experience with a psychologically impactful event; (2) psychological understanding or moral judgment of behaviors; (3) perception of service weaknesses; (4) anxiety and frustration and other emotional responses; (5) belief of what management is best; (6) self-perception of professional capacity. The findings point to a unique, remarkable experience that generates acute emotions, sometimes antagonistic and long-lasting, and little discussed. It is necessary to develop a training on the subject to safeguard the patient's and team's safety when facing a crisis. The way professionals understand and explain the origin of the conflicting behavior; how they regulate their own emotions, besides the improvement in verbal approach skills and in the interpersonal relationship with the patient must be worked on. It is also pointed out the need to advance in the discussions about the mental health network, the training of mental health care workers, and the psychiatric reform, thinking in an articulated manner the issues that affect the work in act, and that can potentiate the coercive approach of the patient in the services.